Ocular Involvement and Blindness Secondary to Linear IgA Dermatosis - Cinthya Ramos-Castellón; Gabriela Ortiz-Nieva; Fernando Fresán; Leonardo Villalvazo; Yonathan Garfias; Alejandro Navas; María C. Jiménez-Martínez (Journal of Ophthalmology)
A 43-year-old man with linear immunoglobulin A (IgA) dermatosis associated with gluten intolerance presented with progressive vision loss, pain and photosensitivity in both eyes. His visual acuity was light perception (LP) in both eyes. A physical examination revealed bullous, papular lesions with erythematous borders in periocular tissues, limbs, and thorax. Slit-lamp examination showed conjunctival hyperemia, fibrosis, corneal opacification, and vascularization with epithelial defects. Immunofluorescent skin and corneal surface biopsy studies showed linear IgA deposits. The patient was treated with keratolimbal allogenic transplantation and cryopreserved amniotic membrane in the right eye. Regardless of the treatment he persisted with torpid evolution developing retinal and choroidal detachments. After these events he was started on intravenous immune globulin (IVIG) and showed very slight improvement in ocular surface. These types of blistering diseases are rare in the eye. Even when adequate local treatment is given, systemic treatment is mandatory and ocular prognosis can be unsatisfactory.